Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1016/j.jconrel.2018.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Advax augments B and T cell responses upon influenza vaccination via the respiratory tract and enables complete protection of mice against lethal influenza virus challenge

Abstract: Administration of influenza vaccines via the respiratory tract has potential benefits over conventional parenteral administration, inducing immunity directly at the site of influenza exposure as well as being needle free. In this study, we investigated the suitability of Advax™, a stable particulate polymorph of inulin, also referred to as delta inulin, as a mucosal adjuvant for whole inactivated influenza vaccine (WIV) administered either as a liquid or dry powder formulation. Spray freeze-drying produced Adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 58 publications
1
38
0
Order By: Relevance
“…Advax is a particulate polysaccharide adjuvant with a low inflammatory profile that has proven to be safe and a strong inducer of vaccine immunogenicity in humans, thus making it an ideal candidate for mucosal administration [18] [19]. Notably, it was recently shown to provide safe and effective enhancement of influenza vaccine immunity when administered via the intrapulmonary route in different animal models [20,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Advax is a particulate polysaccharide adjuvant with a low inflammatory profile that has proven to be safe and a strong inducer of vaccine immunogenicity in humans, thus making it an ideal candidate for mucosal administration [18] [19]. Notably, it was recently shown to provide safe and effective enhancement of influenza vaccine immunity when administered via the intrapulmonary route in different animal models [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…https://doi.org/10.1101/2020.02.25.964312 doi: bioRxiv preprint 15 effect of the vaccine was associated with targeted expansion of lung-resident T RM and was dependent on IL-17 recruitment of phagocytic cells to the lung and enhanced priming of T cells in the mLN. As Advax-containing vaccines have proven safe and immunogenic in human trials against viral infection and allergy [19,45,46] and are safe and effective in pre-clinical trials as inhaled formulations [21], CysVac2/Advax is a promising candidate for assessment of safety, immunogenicity and efficacy as a pulmonary vaccine in human subjects.…”
mentioning
confidence: 99%
“…Also, the biological activity of BLP was found to be well preserved during SFD. Previous studies have shown that administration of BLP or Advax adjuvanted influenza vaccine formulations via the respiratory tract results in substantial augmentation of systemic and mucosal immune responses in mice [16,[43][44][45][46]. In this study we showed that after active administration, systemic immune responses (serum IgY titers) after one immunization were predominantly enhanced by Advax whereas after two immunizations they (serum IgY, HI titers, micro-neutralization titers) were mainly enhanced by BLP.…”
Section: Discussionmentioning
confidence: 48%
“…The virus was produced in the allantoic cavity of 11-day-old embryonated hens' eggs. The virus was purified and inactivated as described by Tomar et al to obtain WIV [21,22]. WIV was derived from the same strain as previously published [21,22].…”
Section: Virus Preparationmentioning
confidence: 99%
“…The virus was purified and inactivated as described by Tomar et al to obtain WIV [21,22]. WIV was derived from the same strain as previously published [21,22]. The size of WIV (around 185 nm) together with other physico-chemical properties of WIV were described in these papers.…”
Section: Virus Preparationmentioning
confidence: 99%